Quality Evaluation of Venezuelan Higher Education - Lilian Pineda (Ksiegarnia Akademicka Publishing, 2021)
Since 1999, there have been changes in Venezuelan higher education, such as the establishment of new forms of university access, attempts to reform Universities Act, enacting a new Organic Education Law, among others. Consequently, one wonders what the real situation of Venezuelan higher education subsystem is and whether it has been building a new model of higher education in the last decade. In the present study, we attempt to answer these questions, in light of specific policies and plans established by the State regarding the education sector, quality management strategies, administrative‑governance organization basic forms, and the methodological framework for assessing quality.